EFFICIENCY OF DIGITALIZATION IN THE AGRICULTURAL SECTOR - CHUIENKO, VITALII (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The intensive development of information technologies creates all the prerequisites for the active implementation of digital technologies in all sectors of the Ukrainian agro-industrial complex. The article analyzes the effectiveness of digitalization in the agricultural sector. The necessity of using a digital platform, especially for small and medium-sized agricultural enterprises, is determined. The role of the state on the path of digitalization as a data user and a key supplier of data to the private sector is outlined. The benefits of using a digital platform in the agricultural sector are analyzed. The introduction of digital technologies allows producers to quickly find, collect and analyze information that will ensure effective decision-making. An analysis of the current state of digitalization of the agro-industrial complex makes it possible to identify priority areas for the introduction of digital technologies in order to reduce labor costs and improve production processes. Access to information data is one of the most important indicators for the effective digitalization of the agricultural sector. The importance of creating databases and ensuring their protection is considered. Digitalization in agriculture ensures continuous collection and analysis of the data obtained in order to identify problematic issues. Modern digitalization of production processes allows optimizing and increasing the profitability of production. In analyzing the need for digitalization of the agricultural sector, the article provides examples of the practical use of smart technologies by domestic agricultural enterprises: integrated management of machinery; systemic fuel accounting; work performance accounting; precision farming; smart farming; digital farming; and the use of robotic milking of cows. The performance indicators for the application of digitalization in the agro-industrial complex are determined: optimization of financial, time and resource costs; increase in the accuracy of calculations and planning of economic activities; and increase in production productivity. The obstacles that slow down the introduction of digital technologies are identified.